Avaliação da conformidade de blocos cerâmicos para alvenaria de vedação produzidas na Região Integrada de Desenvolvimento da Grande Teresina - Rêgo, Vilson Ribamar (2008)
This research presents an outlook of the industries of red ceramic in the region next to the city of Teresina and an analysis of the ceramic products producted in this pole. The microregion investigated possesses 13 boroughs where were identified 32 ceramic in operation, being that 24 are located in Teresina, the ceramic region more important of Piauí, 1 is located in the city of Miguel Leão and 7 is located in Timon city that belongs to the state of Maranhão. The majority of ceramics are pulverized in these two cities, Teresina and Timon , responsible by a largely production independent of distance between fabric and consumer market. Furthermore, there is an artisanal production realized in other boroughs, mainly manual conformation bricks, where are producted diverse types of handicraft and ceramics utilitarian. The objective of this research is to evalue the conformity of ceramic blocks for brick of obstruction made by red ceramic industry of microregion at studying, verifying their pontentialities and adequacy in terms of production. In this research universe made a search of ceramic industries related to the Foundation CEPRO (Foundation Center of Research Social and Economic of Piauí). For the analysis of the ceramic products , were colected 60 crude bricks sample in three industries for their characterization, and 39 burned bricks sample for the Evaluation of Conformity. The results of the characterization made reached a accetptable standard in all formulations and temperature studied. The burned samples were applied to the geometric, physical and mechanical assays according to the ABNT standards (Brazilian Association of Technical Standards). The results of the physical assays showed that all the samples are at the same band recommended by standard. However, through the geometric assays just two industries did not present results according to the standard, due to lack of control in their process such as in their equipments. Taking into account the mechanical properties, only one industry investigated was not according to the standard